PTU-138 Feasibility Study of Volatile Organic Compounds in Constipation in Parkinson's Disease. (17th August 2016) - Qureshi, S; Bond, A; Iwanejko, L; Probert, C
Abstract : Introduction: Patients with Parkinson's disease (PD) have constipation. Constipation often precedes the classical motor signs. Enteric neuropathy may play a role of the aetiology of PD. Exposure to fungi is a risk factor for PD: in vitro models have shown specific fungi-produced volatile organic compounds (VOC), 1 octen-3-ol and 2 octanone, may cause loss of dopaminergic neurones in fruit flies. We propose the hypothesis that intestinal fungal metabolites may a risk factor for PD. This study assessed the feasibility of performing faecal VOCs analysis in people with PD and controls. Methods: 8 patients with diagnosed PD were invited from an exercise class (Dancing for Parkinson's). Their partners/carers were also invited as aged-matched controls. Samples from lab volunteers (14) were also analysed. Patients or controls that had taken any antibiotics or antifungals in the 4 weeks prior to sampling were excluded. VOCs from 2 aliquots per donor were extracted using Solid Phase Micro Extraction (SPME), separated by gas chromatography–mass and analysed by gas spectrometry (GC-MS). VOCs were identified using AMDIS and comparison with the current NIST library of mass spectra. Reported were prepared using Metab, and statistical analysis undertaken using Metaboanalyst software. Results: All 8 PD patients provided samples, despite their constipation. 5 of 6 aged-matched controls provided samples. The average result from the paired technical replicates was used for statistical analysis. There were significantly fewer VOC in samples from PD patients (63), than from controls (74, p < 0.007). Young and older controls had a similar number of VOCs (80 and 71 respectively, p = ns). The abundance of VOCs in PD and all controls was compared: 33 differed, 7 of which persisted after correction for multiple comparison, including 2 octanone. Conclusion: The study of VOCs in people with constipation is feasible. Those with constipation have fewer VOCs that controls as a whole. There were clear differences in the VOCs from patients with Parkinson's disease in the control group. One of the VOCs that was increased, 2 octanone, in Parkinson's disease is a fungal metabolite that causes damage to dopaminergic neurones in an insect model. More work is necessary to explore the association between PD: a full study will need to include more patients and controls with constipation. Disclosure of Interest: None Declared